Association Between Exclusive Breastfeeding and Nutritional Status of Infants Aged 6–8 Months at Tambakrejo Health Center, Sidoarjo: A Cross-Sectional Study - Marsyanda Daradinanti; Taufiqurrahman; Nuning Marina Pengge; Riezky Faisal Nugroho (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Exclusive breastfeeding plays a crucial role in preventing malnutrition in infants, yet its coverage remains suboptimal in Indonesia, including in new health centers like Tambakrejo. This study aimed to provide evidence-based insights to support maternal and child nutrition programs. A cross-sectional analytical design was used involving 55 infants aged 6–8 months selected through saturated sampling at Tambakrejo Health Center, Sidoarjo. Data were collected via structured interviews and anthropometric measurements, then analyzed using univariate and bivariate analysis with the Spearman test. Results showed that 63.6% of infants received exclusive breastfeeding, and most had normal nutritional status based on weight-for-age (96.4%), length-for-age (94.5%), and weight-for-length (80%). A significant association was found between exclusive breastfeeding and weight-for-length (p=0.043), while no significant relationship was found with weight-for-age (p=0.058) or length-for-age (p=0.270). These findings indicate that exclusive breastfeeding may help prevent acute malnutrition. Health workers are encouraged to enhance education and promotion of exclusive breastfeeding, while future research should consider factors such as complementary feeding and disease history using longitudinal methods for a more comprehensive understanding.